Transforming food systems: heifer international’s inspiring isvit to IITA - International Institute of Tropical Agriculture (International Institute of Tropical Agriculture, 2025)
Join us as we recap the impactful visit on October 16, when IITA welcomed a delegation from Heifer International to discuss potential collaborations aimed at transforming food systems in Nigeria. The team, led by Dr. Lekan Tobe, the Country Director, included Grace Dangana, the Signature Programme Technical Lead, Heifer International Nigeria, Onyekachi Ayevbuomwan, Program Lead, Heifer International Nigeria, and Engr. Gift Umor, Crop Programme Coordinator, Heifer International Nigeria. Together with IITA’s scientists and program leads, they explored innovative strategies for advancing sustainable agriculture. Don't miss this insightful interaction that aims to shape the future of food production in the region!